Applied Econometrics Using the SAS System - Ajmani, Vivek B. (Wiley, 2012)
The subject of econometrics involves the application of statistical methods to analyze data collected from economic studies. The goal may be to understand the factors influencing some economic phenomenon of interest, to validate a hypothesis proposed by theory, or to predict the future behavior of the economic phenomenon of interest based on underlying mechanisms or factors influencing it. Although there are several well-known books that deal with econometric theory, I have found the books by Badi H. Baltagi, Jeffrey M. Wooldridge, Marno Verbeek, and William H. Greene to be very invaluable. These four texts have been heavily referenced in this book with respect to both the theory and the examples they have provided. I have also found the book by Ashenfelter, Levine, and Zimmerman to be invaluable in its ability to simplify some of the complex econometric theory into a form that can easily be understood by undergraduates who may not be well versed in advanced statistical methods involving matrix algebra.